2019
DOI: 10.35940/ijrte.d5365.118419
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Modeling of Structural Organization of Constructive-Heat-Insulating Construction Materials

Shaumarov Said*,
Adilhodzhaev Anvar

Abstract: The article is devoted to the determination of the fractal dimension of the porous surface and further finding the relationship of the fractal dimension with the porosity of cellular concrete. A numerical experiment was carried out aimed at determining the fractal dimension of the structure of cellular concrete in order to clarify the relationship of the latter with its porous structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…V. G. Gagarin [10], W. Feist [11] and others [12][13][14]. An analysis of the results of their research showed that the currently used methods of designing external building envelopes for buildings of this type do not have sufficient scientific justification, and the structural solutions of the walls themselves are rather complicated in technical design, do not take into account the specific climatic, economic and raw materials of the construction areas.…”
Section: Introductionmentioning
confidence: 99%
“…V. G. Gagarin [10], W. Feist [11] and others [12][13][14]. An analysis of the results of their research showed that the currently used methods of designing external building envelopes for buildings of this type do not have sufficient scientific justification, and the structural solutions of the walls themselves are rather complicated in technical design, do not take into account the specific climatic, economic and raw materials of the construction areas.…”
Section: Introductionmentioning
confidence: 99%